Innovative Strategies in Arabic Language Teaching: Enhancing Communicative Competence in Higher Education - Mubarok Fatahillah; Husnul Hafidhoh; Najhah Barnamij (Interdisciplinary Journal of Advanced Research and Innovation, 2026)
This study examines innovative strategies in Arabic language teaching and their role in enhancing students’ communicative competence in higher education. The research was conducted at Sekolah Tinggi Agama Islam Kuningan, Indonesia, using a qualitative case study design. Data were collected through semi-structured interviews, classroom observation, and document analysis involving Arabic language lecturers, students, and academic stakeholders. The findings indicate that innovative Arabic teaching is reflected in five major aspects: communicative teaching orientation, task-based and collaborative learning, digital media integration, affective support for students’ willingness to communicate, and institutional support for pedagogical transformation. The study shows that communicative competence can be strengthened when Arabic learning moves beyond grammar-translation practices and provides students with meaningful opportunities to use Arabic in interaction, discussion, presentation, and contextual tasks. Digital media and mobile learning resources also support vocabulary acquisition, listening exposure, independent practice, and student engagement, although their effectiveness depends on lecturer readiness and pedagogical integration. The study concludes that innovative Arabic language teaching requires an integrated learning ecosystem involving curriculum alignment, lecturer facilitation, interactive methods, digital resources, communicative assessment, and institutional commitment. These findings contribute to the development of Arabic language pedagogy in Islamic higher education and offer practical implications for improving communicative Arabic instruction in Indonesian higher education contexts.